2022
DOI: 10.3390/ijms23137330
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Grade and Survival Expression Biomarkers of Human Gliomas Based on Algorithmically Reconstructed Molecular Pathways

Abstract: In gliomas, expression of certain marker genes is strongly associated with survival and tumor type and often exceeds histological assessments. Using a human interactome model, we algorithmically reconstructed 7494 new-type molecular pathways that are centered each on an individual protein. Each single-gene expression and gene-centric pathway activation was tested as a survival and tumor grade biomarker in gliomas and their diagnostic subgroups (IDH mutant or wild type, IDH mutant with 1p/19q co-deletion, MGMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 61 publications
0
6
0
2
Order By: Relevance
“…Lower expression of LAMA1 has been associated with improved survival in GBM patient datasets, whereas LAMA1 overexpression has been correlated with increased tumor growth in primary GBM (Scrideli et al, 2008; Fiscon et al, 2018). LAMB1 has been described as a promising candidate biomarker in GBM (Zolotovskaia et al, 2022). Low levels of LAMB1 have also been associated with a less invasive tumor phenotype and a better prognosis (Virga et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Lower expression of LAMA1 has been associated with improved survival in GBM patient datasets, whereas LAMA1 overexpression has been correlated with increased tumor growth in primary GBM (Scrideli et al, 2008; Fiscon et al, 2018). LAMB1 has been described as a promising candidate biomarker in GBM (Zolotovskaia et al, 2022). Low levels of LAMB1 have also been associated with a less invasive tumor phenotype and a better prognosis (Virga et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also evaluated the various grades of neuronal cancers along with the molecular biomarkers of the cancer-subtypes having a threshold of AUC > 0.7. The outcomes of these studies have suggested an efficacy of these approaches of the reconstructed pathways that is nearly twice that of the genetic biomarkers [ 171 ].…”
Section: Bioinformatics Tools and Statistical Criteria For Biomarker ...mentioning
confidence: 99%
“…FISH vs. F1CDx: un algoritmo es un conjunto de instrucciones o reglas definidas y no ambiguas, ordenadas y finitas, que permite, típicamente, solucionar un problema, realizar un cómputo, procesar datos y llevar a cabo otras tares o actividades 66 . Con algoritmos basados en SNG 67 se pueden reconstruir vías moleculares que llevan a identificar biomarcadores de expresión de grado tumoral y supervivencia 68 . Con F1CDx es posible utilizar un algoritmo para evaluar la deleción de los brazos completos 1p y 19q a partir de los datos de secuenciación, y para ello se utilizaron 463 muestras de glioma.…”
Section: Tema Centralunclassified
“…GLIO-DNA panel: permite la caracterización molecular de los gliomas a través de la detección simultánea de las principales mutaciones y alteraciones en el número de copias 68 . Se enfoca en variaciones genéticas y cromosómicas específicas que involucran el gen de la IDH1, el remodelador de cromatina ATRX, CDKN2A, pTERT y reconoce la codeleción 1p/19q 72 , la ganancia del cromosoma 7 y la pérdida del cromosoma 10.…”
Section: Tema Centralunclassified